2018
DOI: 10.31234/osf.io/hxstc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Men’s and Women’s Youngest and Oldest Considered and Actual Sex Partners

Abstract: Whereas women prefer slightly older sexual partners, men—regardless of their age—have a preference for women in their twenties. Earlier research has suggested that this difference between the sexes’ age preferences is resolved according to women’s preferences. Earlier research has not, however, sufficiently considered that the age-range of considered partners might change over the life span. Here, we investigated the age limits (youngest and oldest) of considered and actual sex partners in a population-based s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
5
15
0
Order By: Relevance
“…Considering that females are interested in older males, their matching strategy remains expressing an interest in younger females. Other studies have confirmed that females, independently of their age, have a preference for males older than them (Wiederman, 1993;Kenrick, Keefe, Bryan, Barr, & Brown, 1995;Buunk, Dijkstra, Kenrick, & Warntjes, 2001;Buunk, Dijkstra, Fetchenhauer, & Kenrick, 2002;Ní Bhrolcháin & Sigle-Rushton, 2005;Antfolk et al, 2015;Antfolk, 2017). Buunk et al (2001) and Conroy-Beam and Buss (2019) have found that males' age preferences depend on the mating strategy, being age similarity more important for long-term than for short-term relationships.…”
Section: Theoretical Backgroundmentioning
confidence: 90%
See 1 more Smart Citation
“…Considering that females are interested in older males, their matching strategy remains expressing an interest in younger females. Other studies have confirmed that females, independently of their age, have a preference for males older than them (Wiederman, 1993;Kenrick, Keefe, Bryan, Barr, & Brown, 1995;Buunk, Dijkstra, Kenrick, & Warntjes, 2001;Buunk, Dijkstra, Fetchenhauer, & Kenrick, 2002;Ní Bhrolcháin & Sigle-Rushton, 2005;Antfolk et al, 2015;Antfolk, 2017). Buunk et al (2001) and Conroy-Beam and Buss (2019) have found that males' age preferences depend on the mating strategy, being age similarity more important for long-term than for short-term relationships.…”
Section: Theoretical Backgroundmentioning
confidence: 90%
“…1 Studies have shown that male preferences regarding their partners' age change during the life course (Buss & Schmitt, 1993;Buunk et al, 2001;Young et al, 2005;Conroy-Beam & Buss, 2019). On the contrary, women's preference for older males tend to remain pretty much stable (Wiederman, 1993;Kenrick et al, 1995;Buunk et al, 2001Buunk et al, , 2002Ní Bhrolcháin & Sigle-Rushton, 2005;Antfolk et al, 2015;Antfolk, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The depicted individuals originated from four different regions: Mexico, Vietnam, Iraq, and West Africa (Nigeria and Cameroon) and were 22-27 years of age. This is an age were individuals are seen as attractive and sexually active (Antfolk et al, 2015, Antfolk, 2017.…”
Section: Intra-sexual Competition and Anti-immigrant Attitudesmentioning
confidence: 99%
“…Human mate selection has been investigated for decades (e.g., Buss & Barnes, 1986;Symons, 1979;Westermarck, 1891), and, for instance, focused on mating strategies (e.g., Buss & Schmitt, 1993) and mating preferences (e.g., Antfolk, 2017;Kenrick & Keefe, 1992). Still, most of these studies assume that individuals generally enjoy access to a pool of potential mates, and that only personal characteristics or sexual competition limit mating success.…”
mentioning
confidence: 99%